PENGARUH ARTIFICIAL INTELIGENCE (AI) TERHADAP HAK ASASI MANUSIA - Jesslyn, Jesslyn; Ritonga, Raja (LPPM Universitas Bina Bangsa, 2025)
The development of artificial intelligence (AI) technology presents significant challenges and opportunities related to human rights (HAM). Although AI provides great benefits, such as increasing the accuracy of medical diagnoses and adapting educational curricula, its presence also raises serious concerns. Individual privacy is becoming a complex issue with the collection, analysis and use of personal data to guide AI decisions, which can threaten individual privacy and security rights. Additionally, the impact of AI's job replacement raises questions about the economic impact and human employment. Cybersecurity is becoming a serious threat with the misuse of AI by cybercriminals for more sophisticated attacks. In responding to these challenges, it is important to establish strong regulations and ethical guidelines that can protect human rights, reduce bias in algorithms, and ensure fairness in AI decisions. Investments in AI ethics research and increasing public awareness of the impact of this technology are crucial steps to direct AI development in a direction that respects and protects human values. With this holistic approach, it is hoped that we can optimize the benefits of AI technology while mitigating its risks to human rights.